IMPROVING LABOR MIGRATION GOVERNANCE IN UZBEKISTAN: RECOMMENDATIONS BASED ON INTERNATIONAL BEST PRACTICES (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
Uzbekistan has experienced significant labor migration in recent years, with many citizens seeking employment opportunities abroad. However, the country's labor migration governance systems and policies have not kept up with this trend. This article reviews international best practices in labor migration governance and provides recommendations for improving the governance of labor migration in Uzbekistan. The recommendations focus on ensuring the rights and protections of labor migrants, improving the management of labor migration flows, and strengthening institutional capacity and coordination among relevant government agencies.